Normal Myelination of the Pediatric Brain Imaged with Fluid-Attenuated Inversion-Recovery (FLAIR)MR Imaging - Murakami, James W. (AJNR Am J Neuroradiol, 1999)
BACKGROUND AND PURPOSE: As in adult imaging, FLAIR can be applied to pediatric brain imaging, and this requires an appreciation of the normal pediatric brain appearance by FLAIR imaging. The purpose of this study was to describe the MR appearance of the brain in normal infants and young children as demonstrated by fluid-attenuated inversion-recovery (FLAIR) MR imaging. METHODS: We retrospectively examined MR brain studies, interpreted as normal by pediatric radiologists, from 29 patients (aged 1 to 42 months) to catalog the appearance of myelination in multiple brain areas. RESULTS: On T2-weighted images, white matter progressed from hyperintense to hypointense relative to adjacent gray matter over the first 2 years of life. An analogous, although slightly delayed sequence was observed on FLAIR images with the exception of the deep cerebral hemispheric white matter, which followed a triphasic sequence of development. On FLAIR images, the deep cerebral white matter was heterogeneously hypointense relative to gray matter in the young infant, became hyperintense early in the first few months of life, and then reverted to hypointense during the second year of life. CONCLUSION: The normal appearance and development of brain white matter must be taken into account when interpreting FLAIR images of infants and young children.